A Regional Life Cycle Sustainability Assessment Approach and its Application on Solar Photovoltaic. (May 2017) - Li, Tianqi; Roskilly, Anthony Paul; Wang, Yaodong
Abstract: This paper proposes a sustainability assessment method which incorporating life cycle approach and sustainability theory. Northeast region of England is chosen as a case study. The assessment examines the sustainability of regional solar photovoltaic deployment in three categories: techno-economic, environmental and social impacts.